A framework for implementing lean principles in supply chain at healthcare organisations. - Almutairi, Abdulaziz Marzouq (Cranfield University, 2019)
The aim of this research is to develop a framework to implement lean thinking in healthcare supply chain management (HSCM). The framework comprises four implementation phases namely; preparation state, assessment of the current state in terms of lean, developing the desired future state in terms of lean and steady (sustainable) state of new actions taken. The developed framework covers the lean enablers, factors and the barriers that may hinder the lean implementation. The final edition of the framework was validated by three hospitals in Saudi Arabia. In addition, the developed framework includes model to assess leanness maturity of the HSCM. The HSCM leanness assessment model was developed by using multi-grade fuzzy approach. This approach consists of three levels; enablers, criteria and attributes. By using such approach, the HSCM leanness index was calculated and practices for further improvement were identified. Five enablers that are important for implementing lean principles in HSCM were identified. The enablers are medical management responsibility, healthcare supply chain processes management, medical human resource, consumer relationship and supplier relationship. Nine lean barriers that are obstacle lean implementation include: existence of physicians’ preferences, unpredictable patient demand, Inadequate knowledge and lack of understanding lean concept , identify type of waste through HSCM processes (delivering value to the patient), hospital culture and resistance to change, lack of hospital support, commitment and disbelief in lean , scarcity of qualified human resources and lack of training , assessment of the required level of leanness and lack of effective communication and information sharing. Prioritization and proposed solutions to overcome these barriers were provided. HSCM leanness assessment model was developed based on three levels: enablers, criteria, and attributes. Mixed methods has been used as research methodology. The research has started with extensive literature review related to supply chain management and lean with focus on healthcare context. Next, the qualitative method was used during field study by using semi-structured and structured interview to capture the knowledge from experts (data collection). The proposed framework enables decision-makers at healthcare providers to implement lean principles in supply chain management through a step by step process. Implementation of the framework will contribute significantly to improving the supply chain's overall performance, quality of work, reducing cost and eliminating wastes and on-time delivery.
Keywords: Supply chain management; lean; healthcare; assessment; leanness; fuzzy logic; barriers; enablers